The existence of Augmented Reality technology in video games / Nur Farah Dalila Zulkifli ... [et al.] - Zulkifli, Nur Farah Dalila; Al Qudry, Tengku Syed Nabil; Abu Bakar, Nur Fatin Umairah; Othman, Jamal (Unit Penerbitan JSKM, 2023)
Augmented Reality (AR) is a technologically augmented representation of the recreated by using digital visual elements, music, or other sensory stimulation. However, the expenses of making an AR are so high. AR can make people’s lives easier by introducing virtual information. It can also enhance the user’s missing senses through sensory substitution. Games with greater augmented reality capabilities may create worlds that change based on the user’s location. AR may display real-time data from items and allow people to operate them via mobile devices. Touchscreen, voice, or gesture are all options. AR might potentially reveal real-time data coming from items. Pokemon Go and Minecraft Earth are examples of games that have AR elements. Next, AR can increase the knowledge and understanding of users. On the other side, AR can give a negative impact on users. For instance, the tendency in increasing the user’s screen time. One of the differences between AR and VR is their visibility. Augmented Reality has great promise and almost unlimited capabilities. The use of augmented reality has the ability to alter the design dynamic. This paper will discuss the implementation of AR in the gaming industry.